PENGARUH LINGKUNGAN KERJA, STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. INDOMARET CO CABANG NANGKA - Rini Rahmawati; Ni Wayan Eka Mitariani; Ni Putu Cempaka Dharmadewi Atmaja (EMAS, 2021)
Employee performance determines a company can run well or badly, employee performance is needed by a company in running a particular business. Often insolvency companies are caused by poor management and employee performance, while some employee performance influences decrease such as work environment, work stress and work motivation. This study aims to obtain empirical evidence of the influence of work environment, work stress and work motivation simultaneously and partially on employee performance at PT. Indomaret Co Nangka Branch. The population and sample of this research are employees of PT. Indomaret Co Nangka Branch as many as 53 employees. Teknik analysis used is Multiple Linear Regression Analysis. The results showed that the work environment, work stress and work motivation simultaneously and partially had a positive and significant effect on employee performance at PT. Indomaret Co Nangka Branch. Further research can develop this using free variables such as Leadership Style, Work Spirit and Compensation. Suggestions that can be given from the results of this study are that organizations should further improve employee safety, improve employee skills with various other jobs, and increase employee morale in completing work